Physical Exercise in MCI Elderly Promotes Reduction of Pro-Inflammatory Cytokines and Improvements on Cognition and BDNF Peripheral Levels - Manuela Crispim Nascimento, Carla; Rodrigues Pereira, Jessica; Pires de Andrade, Larissa; Garuffi, Marcelo; Leme Talib, Leda; Vicente Forlenza, Orestes; Maria Cancela, Jose; Regina Cominetti, Marcia; Stella, Florindo (Current Alzheimer Research, 2014)
The benefits of physical exercise to reduce low-grade inflammation and improve Brain-Derived Neurotrophic Factor (BDNF) levels and cognitive function became a growing field of interest. Low-grade inflammation is common during aging and seems to be linked to neurodegenerative process. Regular physical exercises can help to reduce pro-inflammatory cytokines levels and to improve BDNF peripheral concentrations. The main goal of this research was to analyze the effects of a 16-week multimodal physical exercise program on peripheral BDNF levels and on Tumor Necrosis-α (TNF-α) and Interleukin- 6 (IL-6) as pro-inflammatory markers in cognitive healthy elderly individuals and in elderly with mild cognitive impairment (MCI). Cognitive functions were assessed by the Montreal Cognitive Assessment (MoCA) prior to and after the intervention. Thirty cognitively healthy participants and thirty-seven MCI participants were assigned to the control (CG) and trained (TG) groups. The TG participated in a multimodal physical training program for a 16-week period. The results showed a significant between-subjects interaction, which indicates the beneficial contribution of training on the reduction of TNF-α (p=0.001) and IL-6 (p<0.001) and on the improvement of BDNF (p<0.001) peripheral concentrations. Cognitive functions also presented significant improvements for MCI trained group (p=0.03). In conclusion, physical exercise was effective to reduce pro-inflammatory cytokines and to improve BDNF peripheral levels, with positive reflexes on cognition. To the best of our knowledge, this is the first study that evaluated longitudinally the effects of a multimodal physical exercises protocol on peripheral concentrations of pro-inflammatory cytokines and cognition performance in elderly MCI individuals.
Keywords: cognition